Reduction of Thermomechanical Stress Using Electrically Conductive Adhesives. (August 2015) - Geipel, Torsten; Rendler, Li Carlos; Stompe, Manuel; Eitner, Ulrich; Rissing, Lutz
Abstract: We compare the thermomechanical stresses in solar cell interconnections based on electrically conductive adhesives (ECA) with soldered joints by using bending experiments and finite element analysis (FEA). Additionally, the influence of an increasing number of busbars is studied. The FEA is validated by measuring the bending of cell strips after cooling down from a single-sided interconnection process. The material parameters are determined by tensile tests, microscopy and nanoindentation. The comparison of ECA and soldering shows that an elastomer with a Young's modulus of below 0.5 GPa is capable of reducing the thermomechanical stress effectively resulting in, approximately, a mean tensile stress in the ECA of 5 MPa, 110 MPa in the ribbon, and a maximum compressive stress in the silicon of 75 MPa. Increasing the number of busbars from three to five leads to a reduction in compressive stresses in the silicon and a slight increase of the peak tensile stress in the busbars.